2019
DOI: 10.1155/2019/9864841
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Efficacy Enhancing and Toxicity Reducing Mechanism of Combination of Aconiti Lateralis Radix Praeparata and Paeoniae Radix Alba in Adjuvant-Induced Arthritis Rats by Metabolomics

Abstract: Combination of Aconiti Lateralis Radix Praeparata (FZ) and Paeoniae Radix Alba (BS) shows a significant effect in rheumatoid arthritis (RA). This study aimed to investigate the efficacy enhancing and toxicity reducing mechanism of combination of them in adjuvant-induced arthritis (AIA) rats by metabolomics. Rats were randomly divided into seven groups, including A (healthy control), B (model control), C1 (therapy group), C2 (efficacy enhancing group), D1 (toxicity group), and D2 (toxicity reducing group), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 60 publications
(58 reference statements)
2
19
0
Order By: Relevance
“…Meanwhile, FLS is considered to be the main cellular source of COX-2 in synovial tissue and produce PGE2, which mediates the pain and in ammation in RA (Amin et al, 1999). Notably, in previous research, we have demonstrated that FLA signi cantly alleviated the symptoms of arthritis in AIA mice (Xie et al, 2019). This study found that FLA effectively inhibited the expression and synthesis of pro-in ammatory mediators in IL-1β-induced HFLS-RA.…”
Section: Discussionmentioning
confidence: 53%
“…Meanwhile, FLS is considered to be the main cellular source of COX-2 in synovial tissue and produce PGE2, which mediates the pain and in ammation in RA (Amin et al, 1999). Notably, in previous research, we have demonstrated that FLA signi cantly alleviated the symptoms of arthritis in AIA mice (Xie et al, 2019). This study found that FLA effectively inhibited the expression and synthesis of pro-in ammatory mediators in IL-1β-induced HFLS-RA.…”
Section: Discussionmentioning
confidence: 53%
“…Currently, increasing attention has been paid to the role of natural herbal extracts with a probable therapeutic effect on the treatment of several diseases, including RA ( 37 , 38 ). For example, Astragalus membranaceus , Tripterygium wilfordii and Radix Paeoniae Alba have been proven to have certain therapeutic effects on RA ( 39 - 41 ). The therapeutic effect of traditional Chinese herbs on diseases mainly depends on a variety of active components.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly used for blood deficiency, irregular menstruation, spontaneous sweating, night sweats, flank pain, abdominal pain, limb pain, headache, and dizziness. 6,7 Previous studies showed that PRA could be used for anti-inflammatory effects, 8 immune regulation, 9 treatment of depression 10,11 and anemia, 12 promotion of peripheral nerve regeneration, 13 and treatment of viral infections. 14 Modern studies of pharmacological mechanisms have found that the main active components of PRA include paeoniflorin, paeonol, paeonin, benzoylpaeoniflorin, albiflorin, oxypaeoniflorin, paeoniflorigenone, benzoic acid, β-sitosterol, and gal-lotannin.…”
Section: Pharmacological Studies On the Active Ingredients Of The Sixmentioning
confidence: 99%